PENGARUH GANGGUAN SEKOLAH TERHADAP KEMAMPUAN KOGNITIF PELAJAR DI INDONESIA - Audris Vondrea Wirduno; Pipit Pitriyan (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
Student absenteeism in schools often poses a disruption to the smooth learning process and negatively impacts educational development and student productivity. This study aims to evaluate the influence of the duration of school disruptions on students' cognitive abilities in Indonesia. Data from the Indonesia Family Life Survey (IFLS) in 2014 was utilized for analysis using the Ordinary Least Squares (OLS) method. The research findings indicate that school disruptions have a significant impact on lowering students' cognitive abilities. This study highlights the importance of reducing school disruptions and improving access to and quality of education to enhance the cognitive abilities of students in Indonesia.